Synthesis and Crystal Structure of 1-(2-(1H-Benzoimidazol-1- yl)ethyl)-1H-benzoimidazol-3-ium Chloride Hydrate - YANG, JUN; FENG BI, CAI; YOU, TINGTING; FAN, YUHUA (Asian Journal of Chemistry, 2010)
The crystal structure of 1-(2-(1H-benzoimidazol-1-yl)ethyl)-1Hbenzoimidazol- 3-ium chloride hydrate has been determined by single crystal X-ray diffraction method. The crystal belongs to monoclinic system, space group C2/c with unit cell constants a = 17.093 (3), b = 7.764 (1), c = 13.952 (3) Å, V = 1652.7 (5) Å3, Z = 4, Dc = 1.346 g/cm3, μ = 0.246 mm-1, F (000) = 704, R and wR are 0.0718 and 0.1418, respectively for 1561 unique reflections with 1498 observed reflections [I > 2σ(I)]. The crystal packing is stabilized by C-H…π and π-π interactions.